2021
DOI: 10.20321/nilejbe.v7i17.04
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence and Saving Behavior among Micro and Small Enterprise Owners in Kampala, Uganda: A Moderated Mediation Model of Financial Literacy and Self-Control

Abstract: This research uses cross-sectional data from 430 micro and small enterprise owners in Kampala, Uganda, to examine the indirect effect of financial literacy on the relationship between social influence and savings behavior. In addition, the study examines the moderating effect of self-control on the relationship between financial literacy and savings behavior, in addition to its moderating role in the relationship between social influence and saving behavior. Finally, it studies the moderating effect of self on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…Social influence includes a change in individual emotions, opinions or behavior caused by those in the external environment [63]. Social influence, i.e., friends, university professors, friends and family, can influence an individual's behaviors and principles, and, consequently, might impact the individual's intention and decisions to invest [26]. Student parents are crucial in forming and guiding their children to be financially literate [27]; thus, families play an important role for their children concerning education and inspiration regarding investment behaviors, such as saving and spending.…”
Section: Social Influence and Financial Risky Investment Intentionmentioning
confidence: 99%
See 3 more Smart Citations
“…Social influence includes a change in individual emotions, opinions or behavior caused by those in the external environment [63]. Social influence, i.e., friends, university professors, friends and family, can influence an individual's behaviors and principles, and, consequently, might impact the individual's intention and decisions to invest [26]. Student parents are crucial in forming and guiding their children to be financially literate [27]; thus, families play an important role for their children concerning education and inspiration regarding investment behaviors, such as saving and spending.…”
Section: Social Influence and Financial Risky Investment Intentionmentioning
confidence: 99%
“…Investment awareness leads individuals to gain the knowledge and skills required to make financial decisions [70]. Thus, students can raise their level of investment awareness through many sources, such as peers, parents, friends, social channels and their network members, which can affect their intention to invest [26,71,72]. Weber and Milliman [73] indicated that students with more financial awareness have higher intentions toward investment.…”
Section: Social Influence As a Mediator Between University Education ...mentioning
confidence: 99%
See 2 more Smart Citations
“…This theory is more relevant to demographic variables and retirement planning particularly for public health sector employees, as they most participate in the learning process from their families, peers, community, society and institutions. The theory asserts that the behavior of a person is influenced by interaction between observations of other people, the environment, one's own behavior and one's intellectual capability (Mpaata, Saina & Koskei, 2021). Most of the retirement planning decisions can be attributed to learning process which can be formal or informal.…”
Section: Social Learning Theorymentioning
confidence: 99%